Information communication technology, human capital and economic growth in Malaysia: an empirical analysis - Duasa, Jarita; Mohd Jais, Norjaimah (İstanbul Kültür University, 2018)
The present study aims to investigate the relationship between economic growth, human capital and Information Communication Technology (ICT) in Malaysia in short and long run. Using time series data, the study adopts Autogressive Distributed Lag (ARDL) cointegration technique that applies the bound testing to examine the existence of the relationship between variables. The results suggest that in long run, economic growth is positively determined by capital, labour, ICT and human capital. In the short run, labor, capital and ICT contribute positively and significantly to economic growth but human capital negatively affects growth. The results imply that Malaysian government should undertake better policies that facilitate human capital development along with investment in ICT to boost economic growth of the country in short and long run.